2023
DOI: 10.1186/s12943-022-01704-8
|View full text |Cite
|
Sign up to set email alerts
|

m6A methylation: a process reshaping the tumour immune microenvironment and regulating immune evasion

Abstract: N6-methyladenosine (m6A) methylation is the most universal internal modification in eukaryotic mRNA. With elaborate functions executed by m6A writers, erasers, and readers, m6A modulation is involved in myriad physiological and pathological processes. Extensive studies have demonstrated m6A modulation in diverse tumours, with effects on tumorigenesis, metastasis, and resistance. Recent evidence has revealed an emerging role of m6A modulation in tumour immunoregulation, and divergent m6A methylation patterns ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 232 publications
(250 reference statements)
0
16
0
Order By: Relevance
“…M6A methylation can speed up transcription and participate in proteins translation and mRNA degradation [43][44][45]. m6A methylation modification can directly or indirectly regulate target genes, which can affect biological behaviors such as the proliferation, metastasis, and immune escape of tumor cells [46]. Hence, explaining the relationship between UBE2C and m6A regulators in ACC can enhance our understanding of the mechanism of UBE2C promoting the tumor development.…”
Section: Plos Onementioning
confidence: 99%
“…M6A methylation can speed up transcription and participate in proteins translation and mRNA degradation [43][44][45]. m6A methylation modification can directly or indirectly regulate target genes, which can affect biological behaviors such as the proliferation, metastasis, and immune escape of tumor cells [46]. Hence, explaining the relationship between UBE2C and m6A regulators in ACC can enhance our understanding of the mechanism of UBE2C promoting the tumor development.…”
Section: Plos Onementioning
confidence: 99%
“…Wang et al [ 48 ] found that m6A proteins affect tumour proliferation and metastasis in breast cancer and are strongly associated with patient prognosis. Cao et al [ 49 ] demonstrated the regulatory role of m 6 A methylation in the tumour immune microenvironment (TIME). These studies suggest that PSS as well as some malignant diseases can be treated by targeting m6A mRNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“… 400 402 N6-methyladenosine (m6A) RNA modification, the most common RNA methylation, is closely associated with cancer progression, drug resistance 373 , 374 and cancer immunity. 403 405 Notably, antagonizing m6A modifiers can sensitize tumors to PD-1 blockade in mice. 406 410 However, most agents targeting m6A regulators are still in preclinical development and none has entered clinical evaluation.…”
Section: Immuno-epigeneticsmentioning
confidence: 99%